The KdpD Sensor Kinase of Escherichia coli Responds to Several Distinct Signals To Turn on Expression of the Kdp Transport System - Epstein, Wolfgang (J Bacteriol, 2015)
Kdp, one of three saturable K(+) uptake systems in Escherichia coli, is the system with the highest affinity for K(+) and the only one whose expression is strongly controlled by medium K(+) concentration. Expression is controlled by a two-component system of KdpD, the sensor kinase, and KdpE, the response regulator. There is general agreement that expression occurs when the growth rate of cells begins to become limited by K(+) availability. How K(+) limitation results in expression has been controversial. Studying the roles of the major components of the growth medium shows that KdpD senses at least two distinct signals inside the cell, those of Na(+) and NH(4)(+), and it probably senses other monovalent cations in the cell. KdpD does not sense turgor. IMPORTANCE The expression of the Kdp K(+) transport system of E. coli occurs when cells become limited in their growth rate by the availability of K(+). Cells sense limited K(+) and try to compensate by taking up other monovalent cations, particularly Na(+) and NH(4)(+). These cations are sensed in the cytoplasm by the KdpD response regulator, presumably to stimulate its kinase activity. It is shown that KdpD does not sense turgor, as was suggested earlier.